Construction of uricase-overproducing strains of the methylotrophic yeast Hansenula polymorpha - Dmytruk, K.V.; Dmytruk, O.V.; Sibirny, A.A. (Фактори експериментальної еволюції організмів, 2008)
Strains of Hansenula polymorpha overproducing own uricase (UOX) have been constructed. Uricase gene under the control of the strong H. polymorpha alcohol oxidase promoter was multicopy integrated to the recipient strain H. polymorpha С-105 (gcr1 catX). The recombinant producer characterized by a forty-fold increased UOX enzyme activity (up to 3.36 U ml⁻¹ in cell-free extract) compared to the initial strain.